Malaysian Wood Moulding Sector Some Marketing Aspects - Mohamed, Shukri; Hadi, Yusuf; Yusop, Mohd Zin (1988)
The paper discusses the extent to which the Malaysian wood moulding sector utilises the four marketing mix variables: product, price, promotion and place or channel of distribution. Perceived-value and going-rate pricing methods were the most common pricing methods used by the manufacturers in the sector. Only about 46.7% of the respondents utilised promotional tools to disseminate information about their products. Of this, about 72% advertised their products in trade magazines and journals. The demand for wood moulding remains high in the foreign markets; some 60% of the respondents exported their entire production overseas. Wholesalers and retailers were the immediate distribution channels in the local market, whereas the agents overseas took over the exports. The wholesalers/retailers and government purchases took up about 64% of the domestic sales. The utilisation of the four marketing mix variables were minimal due to the nature of the production method and the target buyers. The sector should adopt a more strategic marketing approach in an effort to maintain the existing markets and capture new ones. This is necessary in view of current depressed world trade in wood products and strong competition from other wood moulding producing countries.